FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KENAIKAN PANGKAT/JABATAN PUSTAKAWAN - Panti, Panti (IQRA: Jurnal Perpustakaan dan Informasi, 2016)
This article describes the factors which affect the promotion of librarians. There are two factors that affect promotions librarian they are external factors and internal factors. Internal factors originating from within the librarian in question, for example: interest, motivation, sincerity, perception became a librarian, education, and interest in working in the library. External factors come from outside librarians are concerned, for example: unit value of the credit rate in grain activities of librarianship are too small, the working environment less conducive, the assessment team less competent in assessing, achievement of top management to librarians less support, appreciation of institutions,to the librarian is very lack .